Discrepancies between longitudinal high slip and lateral low slip friction measurements on prepared ice surfaces - Engström, Niclas; Andrén, Henrik; Larsson, Roland; Fransson, Lennart (Luleå tekniska universitet, Maskinelement, 2009)
The Swedish road administration requested that an independent organization facilitate friction tests with several types of friction measuring devices. These tests were done on the following three surfaces: macro rough and micro smooth ice, macro- and micro smooth ice and macroand micro rough ice. The objective was to evaluate lateral low slip measuring devices against traditional longitudinal high slip devices. This was done by evaluating how they measure road grip, i.e. friction differences between road surfaces and the measuring tire. Tests were performed on Lake Kakel near Arjeplog, northern Sweden on March 18th, 2008. Weather conditions were stable with ice temperatures between -4°C (24.8°F) and -3°C (26.6°F). Tests showed that changes on the ice surfaces were readily detected with all four of the lateral low slip friction measurement devices and the two longitudinal high slip devices. Friction resolutions were higher with low lateral slip devices compared to high longitudinal slip devices. The tires on the devices were of different types and are the main reason for the difference in friction resolution. One major difference was detected; the lateral low slip method measured higher friction between its regular winter tire and the macro rough, micro smooth surfacecompared to the friction on the macro- and micro rough ice. Longitudinal high slip devices measured higher friction between its industrial friction tire and macro- and micro rough ice. Capacity to measure friction in curves was only displayed by the high longitudinal slip devices. Godkänd; 2008; Bibliografisk uppgift: DVD-ROM; 20091029 (henand) CASTT - Centre for Automotive Systems Technologies and Testing